2009
DOI: 10.1042/bst0371293
|View full text |Cite
|
Sign up to set email alerts
|

eEF1A2 and neuronal degeneration

Abstract: Translation elongation factor eEF1A (eukaryotic elongation factor 1A) exists as two individually encoded variants in mammals, which are 98% similar and 92% identical at the amino acid level. One variant, eEF1A1, is almost ubiquitously expressed, the other variant, eEF1A2, shows a very restricted pattern of expression. A spontaneous mutation was described in 1972, which gives rise to the wasted phenotype: homozygous wst/wst mice develop normally until shortly after weaning, but then lose muscle bulk, acquire tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 32 publications
0
25
0
1
Order By: Relevance
“…It is noteworthy that the cell types that switch off eEF1A1 tend to be those that have a strong, stable cytoskeletal organization, such as neurons and muscle. Therefore, Abbott et al (35) raised a hypothesis that these cell types need to switch off eEF1A1 to prevent or modify the cytoskeletal rearranging properties, but for the obvious need to maintain protein synthesis, they use eEF1A2. Supporting this hypothesis, muscle cells switch eEF1A1 back on in response to denervation or toxic injury, reverting back to high levels of eEF1A2 after recovery (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that the cell types that switch off eEF1A1 tend to be those that have a strong, stable cytoskeletal organization, such as neurons and muscle. Therefore, Abbott et al (35) raised a hypothesis that these cell types need to switch off eEF1A1 to prevent or modify the cytoskeletal rearranging properties, but for the obvious need to maintain protein synthesis, they use eEF1A2. Supporting this hypothesis, muscle cells switch eEF1A1 back on in response to denervation or toxic injury, reverting back to high levels of eEF1A2 after recovery (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…No other gene is present in the wasted deletion, and transgenic studies have shown that the EEF1A1 (eukaryotic translation elongation factor 1 alpha 1) Scaggiante B, Bosutti A Atlas Genet Cytogenet Oncol Haematol. 2015;19(4) phenotype is due to loss of eEF1A2 translation activity in muscle (Doig et al, 2013;Abbott et al, 2009). In neuronal cells, an eEF1A1 interaction with the yeast two-hybrid protein K (HYPK), highlights the involvement of HYPK in the regulation of cell growth, cell cycle, unfolded protein response and cell death.…”
Section: Skeletal Muscle Trauma and Motor Neuron Degenerationmentioning
confidence: 99%
“…The extensive roles that translation factors including eIF2B (eukaryotic initiation factor 2B), which is mutated in VWM/CACH, play in learning and memory was also highlighted. Abbott et al [8] showed that loss of a translation elongation factor, eEF1A2 (eukaryotic elongation factor 1A2), causes motor neuron degeneration in mice, providing a good model for motor neuron disease. Expression of eEF1A2 is highly restricted compared with the more ubiquitous eEF1A1, and fits well with the onset of the phenotype.…”
Section: Introductionmentioning
confidence: 99%
“…The final stage in the gene to protein path is translation and Abbott et al [8] (pp. 1293-1297) and Pavitt and Proud [9] (pp.…”
Section: Introductionmentioning
confidence: 99%